Sex og vold: Modeller og terrorister i Bret Easton Ellis’ Glamorama - Nielsen, Henrik Skov (K&K - Kultur og Klasse, 2008)
Sex and Violence: Literary critics have paid very little attention to Bret Easton Ellis’s book Glamorama. In fact no-one I know of has even undertaken the seemingly simple task of finding out what actually happens in the course of the narrative. In this article I will do just that and analyse the book by considering such basic parts of the book as its title, the first and last page and the plot. I will pay special attention to the multilayered violence. Using the distinctions by Slavoj Žižek, to whom I will turn at the end of the article, I will argue that the violence in Glamorama takes place at a subjective, a symbolic and a systemic level at the same time.